Penggunaan Deiksis dalam Novel Arah Langkah Karya Fiersa Besari - Siti Setiawati; Dimas Pratama Rustianto; Asep Muhyidin (Universitas Indraprasta PGRI, 2023)
This research is a study of the use of deixis forms. This study aims to: (1) Describe the use of persona, space, and time deixis in the novel Direction Steps by Fiersa Besari. (2) Describe the relevance of the results of research data analysis to learning the Indonesian language and literature at the senior high school level. This study used a qualitative approach with a descriptive-analytic research design. The data sources in this study are words that contain deixis in the speech between characters in the novel Direction Steps by Fiersa Besari. This study's data collection techniques were tapping, speaking, and note-taking techniques. The results of this study found three forms of deixis, namely persona deixis, spatial deixis, and time deixis, with a total of 85 data findings. The 11 categories of derivatives are as follows: (1) 26 first persona singular, (2) 5 first persona plural, (3) 10-second persona singular, (4) 2-second persona plural, (5) 4 persona data third singular, (6) 3 plural third-person data, (7) 13 demonstrative data, (8) 12 locative data, (9) 4 past data, (10) 3 present data, and (11) 3 future data will comeKeywords: Deixis, qualitative, learning, speech.